Incidentally discovered low‐grade appendiceal mucinous neoplasm: a precursor to pseudomyxoma peritonei. Issue 12 (13th October 2016) - Padmanaban, Vennila; Morano, William F.; Gleeson, Elizabeth; Aggarwal, Anshu; Mapow, Beth L.; Stein, David E.; Bowne, Wilbur B.
Key Clinical Message: Appendiceal mucoceles (AMs) infrequently arise from an underlying malignancy. Treatment has progressed toward a less aggressive approach over time; they can be managed by appendectomy‐only unless pathology reveals malignancy. The ultimate goal of management is to prevent AM rupture, avoiding the syndrome of pseudomyxoma peritonei. Abstract : Appendiceal mucoceles (AMs) infrequently arise from an underlying malignancy. Treatment has progressed toward a less aggressive approach over time; they can be managed by appendectomy‐only unless pathology reveals malignancy. The ultimate goal of management is to prevent AM rupture, avoiding the syndrome of pseudomyxoma peritonei.